Measurement of low dietary fiber intake as a risk factor for chronic constipation in children - Morais, Mauro B. [UNIFESP] (1999)
Background: Scarce information exists regarding dietary fiber intake in children with chronic constipation. the objective of this case-control study was to evaluate the intake of fiber as a risk factor for chronic constipation.Methods: Fifty-two children with a mean age of 6.8 +/- 3.2 years who had chronic constipation were age and gender matched with 52 children with normal intestinal habits. the fiber content of the diet was evaluated with a 24-hour dietary recall. Two tables of fiber composition in foods were used: a Brazilian table, and a table based on the method of the Association of Official Agricultural Chemists (AOAC).Results: According to the Brazilian table, the median intake of fiber (in grams per day) by the constipated and the control groups was 13.8 and 17.3, respectively, for total fiber (p = 0.020), 6.8 and 9.7 for insoluble fiber (p = 0.004), and 6.5 and 7.6 for soluble fiber (p = 0.104). According to the AOAC table, the constipation group (9.7 g/day) also had lower (p = 0.0022) intake of total fiber than the control group (12.6 g/day). the coefficient of correlation between the two tables on fiber content of food was +0.82 (p < 0.001) in the constipation group and +0.86 (p < 0.001) in the control group. the intake of fiber was less than the minimum recommendation (age + 5 g) and statistically associated (p = 0.001) with the constipation group (75.0%) in comparison with the controls (42.5%). the odds ratio was 4.1 (95% confidence limits, 1.64-10.32).Conclusion: Intake of fiber below the minimum recommendation is a risk factor for chronic constipation in children.